IN SITU TRANSESTERIFICATION OF JATROPHA SEEDS: EFFECT OF REACTANT TYPE, STIRRING SPEED AND REACTION TEMPERATURE ON YIELD AND QUALITY OF BIODIESEL - Ika Amalia Kartika, Mohamad Yani dan Dede Hermawan (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACT The objective of this study was to investigate in situ transesterification process which allows direct production of biodiesel from jatropha seeds. The reactant type (methanol and ethanol), the stirring speed (700, 800 and 900 rpm) and the reaction temperature (40, 50 and 60°C) were examined to determine the best performance of the biodiesel production yield and its quality. Generally, the stirring speed and the reaction temperature affected biodiesel production yield. An increase of biodiesel yield was observed as stirring speed and reaction temperature were increased. The reactant type did not affected biodiesel production yield. The highest biodiesel yield for the reactant of methanol (82.2%) and the reactant of ethanol (82.5) were obtained respectively under the stirring speed of 800 and 900 rpm, and the reaction temperature of 50°C. The effects of the reactant type, stirring speed and reaction temperature on biodiesel quality were less important. In all experiments tested, the biodiesel quality was very good. The acid value was below 0.5 mg KOH/g of biodiesel, water and sediment contents were very poor (< 0.05%), viscosity was low (< 3.6 cSt), saponification and ester values were high (> 180 mg KOH/g of biodiesel). In addition, the quality of biodiesel produced under optimum process condition was in accordance with Indonesian Biodiesel Standard. Keywords: transesterification, in situ, jatropha, biodiesel